2018
DOI: 10.1038/s41388-017-0039-5
|View full text |Cite
|
Sign up to set email alerts
|

Activated ALK signals through the ERK–ETV5–RET pathway to drive neuroblastoma oncogenesis

Abstract: Activating mutations of the ALK receptor occur in a subset of neuroblastoma tumors. We previously demonstrated that Alk mutations cooperate with MYCN overexpression to induce neuroblastoma in mice and identified Ret as being strongly upregulated in MYCN/Alkmut tumors. By a genetic approach in vivo, we now document an oncogenic cooperation between activated Ret and MYCN overexpression in neuroblastoma formation. We show that MYCN/RetM919T tumors exhibit histological features and expression profiles close to MYC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 49 publications
4
43
0
2
Order By: Relevance
“…1c). Our findings indicate that ETV5 is regulated downstream of activated ALK through MAPK-signalling, in line with previous studies reporting ETV5 as a downstream target of RAS/MAPK signalling in other cellular contexts 19,27,28 .…”
Section: Alk Fusion Genes Upregulate Etv5 Expression In Alcl and Nsclsupporting
confidence: 93%
See 2 more Smart Citations
“…1c). Our findings indicate that ETV5 is regulated downstream of activated ALK through MAPK-signalling, in line with previous studies reporting ETV5 as a downstream target of RAS/MAPK signalling in other cellular contexts 19,27,28 .…”
Section: Alk Fusion Genes Upregulate Etv5 Expression In Alcl and Nsclsupporting
confidence: 93%
“…After stimulation, upregulated p-ALK levels are rapidly attenuated through dephosphorylation in keeping with previously established signalling kinetics 7 . Using artificial stimulation of the ALK receptor with a monoclonal antibody Lopez-Delisle et al also observed an increase in ETV5 mRNA levels after 6 hours 19 . Therefore, our data are in agreement with the activation of ALK leading to induction of expression of ETV5, as clearly shown here at the protein level.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Not listed [28] PIK3CA inhibitors such as alpelisib [26] Breast cancer PI3K-AKT-mTOR pathway activation ALK TPM3-ALK, TPM4-ALK Inflammatory myofibroblastic tumor ∼ 50% [29] ALK inhibitors [30] such as alectinib [31] Non-small cell lung cancer ALK pathway activation [32] NOTCH1 Loci not specified Aging esophagus 12-80% [33] No specific inhibitors approved Colon cancer Wnt-betacatenin pathway activation [34] KRAS G12V or G12D Arteriovenous malformations in brain ∼ 63% [35,36] MEK inhibitors such as trametinib [16] Colorectal and pancreatic cancer RAS-RAF-MEK-ERK pathway upregulation [15] G12C, G12V, G12A, G12D, G12R…”
Section: H1047l H1047rmentioning
confidence: 99%
“…На экспериментальных моделях установлено, что сочетание мутации ALK, в особенности F1174 [22], c амплификацией MYCN негативно влияет на прогноз, приводя к более быстрому формированию НБ с высокой агрессивностью и повышенной летальностью [23,24]. У детей с НБ, сочетающей амплификацию MYCN с мутацией ALK F1174, летальность достигала 90 % (9 из 10 детей).…”
Section: 9unclassified